1999
DOI: 10.1001/archinte.159.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Close Relation Between Cirrhosis and Gallstones

Abstract: Background: Increased gallstone prevalence and incidence in cirrhosis have already been reported in different series, including a limited number of patients with cirrhosis.Objective: To evaluate the frequency of gallstones and related risk factors in a large series of patients with cirrhosis. Patients and Methods:The cross-sectional study involved 1010 patients with cirrhosis related to alcohol abuse, chronic viral infection, or miscellaneous causes (42%, 48%, and 10%, respectively) in Child class A, B, or C (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(20 citation statements)
references
References 25 publications
2
15
1
2
Order By: Relevance
“…After adjustment for age, LDL-Cho and family history of GD, GD prevalence was still significantly associated with HCV-related cirrhosis in both females and males compared to those with chronic hepatitis or normal biochemistry. Conte et al [30] found that advanced cirrhosis (Child class B and C) was associated with a greater risk for gallstones in cirrhotic patients, and our results likewise demonstrated insignificant association.…”
Section: Discussionsupporting
confidence: 66%
“…After adjustment for age, LDL-Cho and family history of GD, GD prevalence was still significantly associated with HCV-related cirrhosis in both females and males compared to those with chronic hepatitis or normal biochemistry. Conte et al [30] found that advanced cirrhosis (Child class B and C) was associated with a greater risk for gallstones in cirrhotic patients, and our results likewise demonstrated insignificant association.…”
Section: Discussionsupporting
confidence: 66%
“…Considering the Child score is a common indicator for evaluating the severity of liver damage, this result suggests that the incidence of GD is positively associated with the severity of liver damage. This finding is consistent with findings of previous studies (2,6,7). In our present study, the prevalence of gallstones was 27.81% in the 338 Child A patients, 30.32% in the 597 Child B patients, and 36.60% in the 705 Child C patients (p=0.007).…”
Section: Shi Et Al Gallstones Subjected To Liver Transplantationsupporting
confidence: 93%
“…The varying results on the relationship between smoking or drinking and cholelithiasis [7,8,9,10,11] may be due to differences in study population, study design, and method of case detection. Although the biological mechanisms of the relationship between smoking and cholelithiasis are unclear [11], increased liver diseases among the smoker group in this study may have caused increased cholelithiasis since some reports show a close relation between cirrhosis and gallstones [37, 38]. Kono et al [11] reported a significant decrease in the prevalence of gallstone and postcholecystectomy status in moderate and heavy drinkers among Japanese men, but the present study showed no association of alcohol with cholelithiasis.…”
Section: Discussioncontrasting
confidence: 65%